Ionogels in Aqueous Media: From Conductometric Probing of the Ionic Liquid Washout to the Design of More Stable Materials - Sergei Yu. Kottsov; Alexandra O. Badulina; Vladimir K. Ivanov; Alexander E. Baranchikov; Aleksey V. Nelyubin; Nikolay P. Simonenko; Nikita A. Selivanov; Marina E. Nikiforova; Aslan Yu. Tsivadze (ChemEngineering)
Although the most promising applications of ionogels require their contact with aqueous media, few data are available on the stability of ionogels upon exposure to water. In this paper, a simple, easy-to-setup and precise method is presented, which was developed based on the continuous conductivity measurements of an aqueous phase, to study the washout of imidazolium ionic liquids (IL) from various silica-based ionogels immersed in water. The accuracy of the method was verified using HPLC, its reproducibility was confirmed, and its systematic errors were estimated. The experimental data show the rapid and almost complete (>90% in 5 h) washout of the hydrophilic IL (1-butyl-3-methylimidazolium dicyanamide) from the TMOS-derived silica ionogel. To lower the rate and degree of washout, several approaches were analysed, including decreasing IL content in ionogels, using ionogels in a monolithic form instead of a powder, constructing ionogels by gelation of silica in an ionic liquid, ageing ionogels after sol–gel synthesis and constructing ionogels from both hydrophobic IL and hydrophobic silica. All these approaches inhibited IL washout; the lowest level of washout achieved was ~14% in 24 h. Insights into the ionogels’ structure and composition, using complementary methods (XRD, TGA, FTIR, SEM, NMR and nitrogen adsorption), revealed the washout mechanism, which was shown to be governed by three main processes: the diffusion of (1) IL and (2) water, and (3) IL dissolution in water. Washout was shown to follow pseudo-second-order kinetics, with the kinetic constants being in the range of 0.007–0.154 mol−1·s−1.